Detecting cracks due to steel corrosion in reinforced cement mortar using intermodulation generation of ultrasonic waves. (7th June 2021) - Miró, M.; Eiras, J.N.; Poveda, P.; Climent, M.Á.; Ramis, J.
Highlights: Accelerated steel corrosion in mortars increase nonlinearity in ultrasonic waves. Possibility of using non-linear ultrasonic techniques to detect corrosion cracking. Non-linear features (intermodulation products) appear before first visible crack. The greater the degree of damage, the higher the values and variability of R. Statistical analysis of non-linear features allows to establish damage thresholds. Abstract: It has been studied the sensitivity of the technique of intermodulation of ultrasonic waves to detect different damage states of concrete due to embedded steel corrosion. Accelerated corrosion tests have been conducted on reinforced cement mortar specimens, while monitoring the appearance and width evolution of visible surface cracks and performing intermodulation measurements. It has been established a statistically acceptable "upper control limit" for the initial (undamaged) Intensity Modulation Ratio (R) values. After subjecting the samples to the corrosion tests, it was observed that the greater the degree of damage, the higher the value ranges and the variability degree of R.